Mezzo economics analitycal approach as the propulsive part of managerial economics in tourism - Saso Kozuharov (UTMS Journal of Economics, 2011)
Mezzo Economics covers the area between the Micro and Macro Economics and the organizational approach of the economics of the integral economic communities, which are made of microeconomic entities. Mezzo Economics represents an organizational loop between the Macro economic system and Micro Economics. Tourism industry is a typical represent of Mezzo Economics. Mezzo Economics Analytical Approach represents a compositional and methodological approach that make constitution of the basic and derived segments of economics in general and special statistical methodology but its specifics consists on the level that make generalization of generated calculative indicators (in Tourism). Marginal analysis are incorporated changes of the value of the choice of the level of small (infinitesimal) amounts in order to consider whether the functions of the aim is possible to be increased (in case of maximalization) or decreasing (in case of minimalization) in which the manager continues with upgraded adjustments in the variable choice until the moment when there is no possibility for further enhancing.
Keywords: C38; L83; O11; O12; 330; mezzo economics; managerial economics; marginal analysis; tourism cluster; calculative indicators